Accurate Diagnosis of Adnexal Torsion—Not Only for Expert Sonographers: A Retrospective Cohort Analysis. (20th May 2021) - Silber, Michal; Gilboa, Yinon; Perlman, Sharon; Krispin, Eyal; Sukenik, Shai; Shochat, Tzippy; Hadar, Eran; Bardin, Ron
Abstract : Objectives: The aim of the study was to evaluate the clinical and sonographic parameters associated with a correct or incorrect diagnosis of adnexal torsion made by resident/attending physicians who are not expert sonographers. Methods: A retrospective study design included women who presented to the Emergency Department (ED) of a tertiary medical center between 2010 and 2019 with acute lower abdominal pain, who were subsequently diagnosed laparoscopically with adnexal torsion. Women who were correctly diagnosed in the ED by an obstetrician‐gynecologist who was not an expert sonographer were compared for clinical and sonographic parameters with women who were initially incorrectly diagnosed and underwent a second ultrasound examination by an expert sonographer following admission. Results: Of 118 women with surgically proven adnexal torsion, 76 were correctly diagnosed in the ED and 42 were initially incorrectly diagnosed. The correctly diagnosed group was characterized by a significantly shorter mean time from admission to surgery, higher rate of vomiting, shorter duration of abdominal pain, and higher rate of prior torsion ( P < .05). Physicians who made the correct diagnosis utilized more sonographic parameters than those who did not, namely ovarian size, ovarian edema, and Doppler flow. The correctly diagnosed group had a higher rate of bluish‐black (ischemic) adnexa at laparoscopy, but a higher rate of recovery following detorsion. Conclusions: Physicians in the ED should be alerted to the need to address some basic sonographic features when adnexal torsion is suspected. The diagnostic accuracy of adnexal torsion can be improved by utilizing simple sonographic markers, even in the ED setting. Abstract : Access the CME test here and search by article title.